Sustained release and cytotoxicity evaluation of carbon nanotube-mediated drug delivery system for betulinic acid - Tan, Julia Meihua; Govindarajan, Karthivashan; Arulselvan, Palanisamy; Fakurazi, Sharida; Hussein, Mohd. Zobir (Hindawi Publishing Corporation, 2014)
Carbon nanotubes (CNTs) have been widely utilized as a novel drug carrier with promising future applications in biomedical therapies due to their distinct characteristics. In the present work, carboxylic acid-functionalized single-walled carbon nanotubes (f-SWCNTs) were used as the starting material to react with anticancer drug, BA to produce f-SWCNTs-BA conjugate via stacking interaction. The conjugate was extensively characterized for drug loading capacity, physicochemical properties, surface morphology, drug releasing characteristics, and cytotoxicity evaluation. The results indicated that the drug loading capacity was determined to be around 20 wt% and this value has been verified by thermogravimetric analysis. The binding of BA onto the surface of f-SWCNTs was confirmed by FTIR and Raman spectroscopies. Powder XRD analysis showed that the structure of the conjugate was unaffected by the loading of BA. The developed conjugate was found to release the drug in a controlled manner with a prolonged release property. According to the preliminary in vitro cytotoxicity studies, the conjugate was not toxic in a standard fibroblast cell line, and anticancer activity was significantly higher in A549 than HepG2 cell line. This study suggests that f-SWCNTs could be developed as an efficient drug carrier to conjugate drugs for pharmaceutical applications in cancer chemotherapies.